The Relationship Between Agility and Eye-Foot Coordination on the Ball Dribbling Ability of Dewi Sartika High School Futsal Athletes - Adam Aditia; Tatang Iskandar (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This research aimed to determine the relationship between agility and eye-foot coordination with the dribbling ability of Dewi Sartika High School futsal athletes. This type of research is correlational research. The population in this study was 20 players. Using the total sampling technique. Agility data retrieval with shapes, Illinois Agility Test, and Eye-toe coordination with the form Soccer wall volley test. Meanwhile, dribbling ability is assessed using the zig-zag dribbling test. The research results show that 1) There is a significant relationship between agility and dribbling ability. 2) There is a significant relationship between eye-foot coordination and dribbling ability. 3) A significant relationship exists between agility, eye-foot coordination, and dribbling ability